2013
DOI: 10.1177/003172171309500211
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Student Interest in Science

Abstract: Adults could do much more to excite students about science as a subject and encourage their interest in science careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
2
19
0
1
Order By: Relevance
“…These findings are consistent with the literature regarding developing student interest in STEM by creating hands-on, relevant activities for students to pursue (Aschbacher et al 2013). However, it is also clear from this study that not all activities are equal across ages or grade levels of students.…”
Section: Conclusion and Future Studysupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with the literature regarding developing student interest in STEM by creating hands-on, relevant activities for students to pursue (Aschbacher et al 2013). However, it is also clear from this study that not all activities are equal across ages or grade levels of students.…”
Section: Conclusion and Future Studysupporting
confidence: 91%
“…Many previous studies have addressed ways to improve STEM interest in students. In general, researchers have concluded that more students might be interested in learning science if opportunities were more personally relevant and provided more space to explore and develop who the students might want to be (Aschbacher et al 2013). Student-centered active learning has been shown to improve long-term knowledge retention and deep understanding (Bonwell and Eison 1991;Gallagher 1997;Akinoglu and Tandogan 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Is there a direct relationship between students’ understanding of the scientific process and their interest in a scientific career? Studies have already shown a connection between student self-concept, defined as a student’s perceived ability to do well in a subject, and its crucial role in student success (Lewis, Shaw, Heitz, & Webster, 2009; Aschbacher, Ing, & Tsai, 2013). One study found that “the strongest predictor of students’ [Science/Engineering/Math] career interests in grades 7 to 9 and their aspiration trajectory over time were the questions about confidence as a science learner” (Aschbacher et al, 2013, p. 48).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the challenge of introducing complex academic language, educators face the daunting task of sparking interest in a discipline that may not appeal to many students; they fail to find relevance in the discipline of science (Aschbacher et al, 2013). This study indicated that the use of visuals contributed to a positive attitude concerning the content and the methods of intervention.…”
Section: Relation Of the Results To The Literaturementioning
confidence: 91%
“…Recent research points to various explanations of this reluctance, including, but not limited to, difficulty of subject matter, demands of student time in learning science, less practicality, broadness of science content, lack of sponsorship for science students, and the methods of knowledge transmission from the teacher/text to the student (Adu- Gyamfi, 2013). Many students believe that science is uninteresting, difficult to understand, and irrelevant to everyday life (Aschbacher, Ing, and Tsai, 2013). Willsher and Penman (2011) conducted a study in rural Australia for the purpose of bringing science instruction opportunities to students who lived in an isolated, impoverished region and had not received effective science instruction.…”
Section: Students' Interest and Limitationsmentioning
confidence: 99%